Spatial-temporal patterns and attribution of evapotranspiration in the Middle Yellow River Basin under changing environments - Bo Liu; Shouzhang Peng; Yongxia Ding; Qinggong Han (Journal of Hydrology: Regional Studies)
Study region: The Middle Yellow River Basin (MYRB) Study focus: Environment changes, including human activities (i.e., underlying surface changes) and climate change, have significantly influenced evapotranspiration (ET) processes. However, in the MYRB, research on how ET and its components respond to environment changes remains limited. Therefore, it is urgent to investigate the contributions of climate and underlying surface changes to ET and its components variations, along with the influencing factors on spatial distribution. This study investigated the spatial-temporal patterns of ET, transpiration (T), and transpiration fraction (TF) in the MYRB and conducted an attribution analysis of their spatial distribution and temporal dynamics, utilizing the parameter-calibrated SiB2 model. New hydrological insights for the region: The combined results of the three methods indicated that land cover type (LC), precipitation, and leaf area index (LAI) are the most significant factors influencing ET, while LC, LAI, and the fraction of photosynthetically active radiation primarily affect T and TF. In the MYRB, ET, T, and TF exhibited higher values in the southeast and lower values in the northwest, with a general increase from 2000 to 2020. Compared to climate change, underlying surface changes were the primary drivers of increases in ET, T, and TF, with contributions of 168.3 %, 86.0 %, and 68.6 %, respectively. LAI increase predominantly led to ET, T, and TF increases, with T contributing most to ET growth.